India’s Majoritarian Nationalism: Challenge to Pluralism and Inclusion - Mir, Irfan Ahmad (PT FORMOSA CENDEKIA GLOBAL, 2025)
India, one of the most diverse and plural societies in the world, is witnessing a significant erosion of its liberal-secular foundations as enshrined in its Constitution. The explosive growth of radical right-wing forces poses a grave threat to pluralism, as attacks on Muslims, Dalits, Adivasis, and other marginalized groups often go unpunished. In a multicultural society, differences are inevitable, but these differences are increasingly being manipulated to incite organized conflicts and violent outbursts. Majoritarian ideologies are being imposed on minority cultures, exacerbating the insecurity of non-dominant groups through targeted violence such as mob lynchings. This study highlights the urgent need to confront these trends to safeguard India's democratic ideals, restore pluralism, and revitalize the nation’s institutions against the rise of extremist forces.